COVID- 19 AND SOCIO-ECONOMIC ACCUMULATION IN MAKASAR - T. R. Fahsul Falah; Yenita Sandra Sari; Haroon Bakari; Saeid Jafari (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The Covid-19 pandemic as a problem in the world today is an evaluation of the balance of the life order between humans and nature. Prevention efforts are needed in the process of human- to-human transmission, so that the spread through communities, households, the surrounding environment, and health facilities can be controlled. New habits that have not been able to change people's lifestyles to refrain from group activities or gatherings, there are still infections that spread to each other so that independent isolation is only applied at home, it is prohibited to carry out any activities outside. Socio-economic conditions and individual and natural factors provide relevance in dealing with the Covid-19 pandemic. The research method used is qualitative research by reviewing the results of research from review articles related to the research objectives, namely 2019 and 2020. The results of the study show that the conditions and socio-economic factors, both individual and natural, provide relevance to efforts to deal with the Covid-19 pandemic. Not only the government but the community, as part of an effort to maintain the health of themselves and others, there is awareness to follow the recommended rules set by the competent party to control the pandemic. Keywords: socio-economic, crisis, global